Pengembangan Algoritma Programa Pembatas untuk Penjadwalan Job-Shop - Kurniawan, Bobby (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2021)
This research addressed the job-shop scheduling problem in a manufacturing company. The objective is to minimize the makespan. Constraint programming approach is developed to solve the problem. The result obtained from constraint programming is better than that of currently applied by the company. The constraint programming approach is also tested on several randomly generated instances.